Identification and monitoring of oil pipeline spill fire using space applications - Gbenga, Ogungbuyi Michael (Department of Electrical Engineering, 2019)
Oil pipeline spills in the Niger Delta cause a great deal of environmental damage to sensitive ecosystems and losses of many millions of dollars to the Nigerian economy every year. These spills occur along the routes of pipeline infrastructure and other oil facilities like flowlines, trunk lines, flow stations, barges, well heads etc. The causes of these spill events include: operational or maintenance error, ageing oil facilities, as well as acts of deliberate sabotage of the pipeline equipment which often result in explosions and fire outbreaks. In this project, we have investigated whether satellite observations could be used to detect these oil pipeline fires. The Nigerian National Oil Spill Detection and Response Agency (NOSDRA) database contains a total of 10 072 oil spill reports from 2007 to 2015. The space-based approach we considered in this dissertation included the use of data gathered by the Moderate Resolution Imaging Spectroradiometer (MODIS) on NASA’s Terra and Aqua satellites, which recorded 85 129 active fire hotspots in the Niger Delta from 2007 to 2015. Since the oil spill reports serve as validation data for these oil spill fires, we explored the capability of the MODIS instrument to study the spatio-temporal correlation between spills and fire events by attempting to investigate whether the largest spills by volume that resulted in fires could be detected from space in near-real time. Although the NOSDRA oil spill reports are plagued with several irregularities from the Joint Investigation Visits by the joint task force who visit spill sites, our approach in this dissertation automated the filtering process of the raw database to meet our research goal and objective. This study confirms that, indeed, fires resulting from oil spills are detectable using the MODIS fire products. For 43 of the largest spill events, we were able to establish a spatio-temporal correlation of spill incident reports with MODIS fires clearly associated with the oil pipeline infrastructure. Our study also shed light on the spatial and temporal characteristics of non-pipeline fires in the study area.